Principles of synaptic encoding of brainstem circadian rhythms - Forrest J. Ragozzino; Ilia N. Karatsoreos; James H. Peters (Experimental Physiology)
Abstract Circadian regulation of autonomic tone and reflex pathways pairs physiological processes with the daily light cycle. However, the underlying mechanisms mediating these changes on autonomic neurocircuitry are only beginning to be understood. The brainstem nucleus of the solitary tract (NTS) and adjacent nuclei, including the area postrema and dorsal motor nucleus of the vagus, are key candidates for rhythmic control of some aspects of the autonomic nervous system. Recent findings have contributed to a working model of circadian regulation in the brainstem which manifests from the transcriptional, to synaptic, to circuit levels of organization. Vagal afferent neurons and the NTS possess rhythmic clock gene expression, rhythmic action potential firing, and our recent findings demonstrate rhythmic spontaneous glutamate release. In addition, postsynaptic conductances also vary across the day producing subtle changes in membrane depolarization which govern synaptic efficacy. Together these coordinated pre‐ and postsynaptic changes provide nuanced control of synaptic transmission across the day to tune the sensitivity of primary afferent input and likely govern reflex output. Further, given the important role for the brainstem in integrating cues such as feeding, cardiovascular function and temperature, it may also be an underappreciated locus in mediating the effects of such non‐photic entraining cues. This short review focuses on the neurophysiological principles that govern NTS synaptic transmission and how circadian rhythms impacted them across the day.